2022
DOI: 10.1038/s41467-022-28512-4
|View full text |Cite
|
Sign up to set email alerts
|

Superior Colliculus to VTA pathway controls orienting response and influences social interaction in mice

Abstract: Social behaviours characterize cooperative, mutualistic, aggressive or parental interactions that occur among conspecifics. Although the Ventral Tegmental Area (VTA) has been identified as a key substrate for social behaviours, the input and output pathways dedicated to specific aspects of conspecific interaction remain understudied. Here, in male mice, we investigated the activity and function of two distinct VTA inputs from superior colliculus (SC-VTA) and medial prefrontal cortex (mPFC-VTA). We observed tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…Evidence suggests that these loops have not only motor but also purely cognitive, functions which have been linked with ASD and other DD (Sathyanesan et al, 2019 ). Apparently, several SC brainstem, thalamic, and basal ganglia loops modulate emotional, sensory, and motor variables in order to make automatic decisions in saccade production (Caligiore et al, 2013 ; Thurat et al, 2015 ; Solié et al, 2022 ). Evidence indicates that following Bayesian instead of “winner takes all” rules, the motor reaction produced by interacting forces at the SC reflects a saccade choice instead of a simple saccade vector (Basso and May, 2017 ).…”
Section: The Brainstem and The Scmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that these loops have not only motor but also purely cognitive, functions which have been linked with ASD and other DD (Sathyanesan et al, 2019 ). Apparently, several SC brainstem, thalamic, and basal ganglia loops modulate emotional, sensory, and motor variables in order to make automatic decisions in saccade production (Caligiore et al, 2013 ; Thurat et al, 2015 ; Solié et al, 2022 ). Evidence indicates that following Bayesian instead of “winner takes all” rules, the motor reaction produced by interacting forces at the SC reflects a saccade choice instead of a simple saccade vector (Basso and May, 2017 ).…”
Section: The Brainstem and The Scmentioning
confidence: 99%
“…Other molecules linked with specific behavioral innate approach, defensive, or attack responses triggered by the SC and related to ASD pathogenesis are acetylcholine (Tokuoka et al, 2020 ), endogenous opioids (da Silva et al, 2013 ), dopamine (Redgrave, 2010 ; Solié et al, 2022 ), corticotropin-release hormone (Daviu et al, 2020 ), adrenergic SC receptors and norepinephrine (Iigaya et al, 2012 ; Li et al, 2018a ; London, 2018 ), and glutamine (Barbano et al, 2020 ).…”
Section: Correlations Between Asd and Sc Disruptionsmentioning
confidence: 99%
“…Ablation studies have shown that while the cortex allows for discrimination of sensory inputs, the SC is necessary to initiate movements toward these events 13 . Recently, this subcortical area has been implicated in influencing social behaviors and has been purported to lead to neurodevelopmental disorders such as Autism Spectrum Disorder (ASD) [14][15][16][17] . Although many studies have shed light on SC function, its microcircuitry and formation continue to be poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…As the avian homolog of the mammalian superior colliculus (SC), the tectum is the major subpallial (subcortical) center of multimodal visuo-auditory integration and motor coordination8487. Recent studies have shown that SC has orientation columns88 and contributes to social interaction89, thus its signal processing could be almost on par with those in the visual cortices. Even after the correspondence between ASD and the integrative nature of SC was theoretically argued for51,90, the link has not been experimentally addressed.…”
Section: Discussionmentioning
confidence: 99%